PERFORMANCE OF BIOCLIMATIC ARCHITECTURE IN BUGIS VERNACULAR HOUSING: A CASE STUDY OF JIDA AND LAMMADA HOUSES - Agung Murti Nugroho (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2021)
Bioclimatic architecture is composed of climate-responsive knowledge in vernacular buildings as an effort to create comfortable conditions. This study aims to evaluate the suitability of the application of bioclimatic design to the performance of the thermal environment in one type of Bugis house. The method used is visual assessment and measurement of temperature and humidity in the case studies of Jida and Lammada houses, South Sulawesi. The results of visual observations show the accuracy of the bioclimatic design on the volume and slope elements of the roof; wall type and material; floor height and shade tree layout. The performance of the thermal environment in the living room and bedroom of Lammada house is better than similar rooms at Jida house. The bioclimatic elements that affect the performance of the thermal environment are the volume of the roof, the type and material of the walls and the height of the floor.